Pengaruh Employee Stock Ownership Program (ESOP), Ukuran Perusahaan, dan Struktur Modal Terhadap Kinerja Keuangan Perusahaan Pada Perusahaan Non Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022: Pada Perusahaan Non Keuangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022 - Suherman, Arya Thresna Hermawan; Khairunnisa, Khairunnisa (Politeknik Ganesha Medan, 2024)
Financial performance refers to the effectiveness of capital utilization and operational efficiency of a company. The fluctuation of a company's revenue and profits will impact its financial performance. However, an increase in revenue doesn't necessarily guarantee a rise in profits. Maintaining a strong financial performance is crucial for a company, as it acts as an attraction for potential investors to invest in the company. This research aims to examine the influence of an employee stock ownership program (ESOP), company size, and capital structure on the financial performance of the company. The research employs a quantitative methodology. Data for the research is obtained from secondary sources, primarily financial reports. The target population consists of non-financial companies listed on the Indonesia Stock Exchange. Data is processed through purposive sampling. The sample size includes 13 companies within the period of 2017-2022, resulting in a total of 78 observations. The research findings indicate that company size and capital structure have a positive impact on the financial performance of the company. Conversely, the employee stock ownership program (ESOP) does not show a significant influence on the company's financial performance.